DETEKSI BAKTERI Escherichia coli DALAM AIR MINUM ISI ULANG YANG DISTERILISASI ULTRAVIOLET DI WILAYAH KECAMATAN JAGAKARSA - Rachmawati, Rezki; Muzajjanah, Muzajjanah; Rustam, Yoswita (LPPM Universitas Negeri Jakarta, 2015)
Refill Water Depot is currently more widely circulated and used as an alternative drinking water supply by the public. However the still unclear about the quality of the drinking water refill generated primarily of biological content. Parameters of biological contamination in drinking water caused by the Escherichia coli and coliform bacterium. This study aims to identify E. coli and coliforms in drinking water refill. Refill drinking water samples obtained from 16 drinking water refill from Jagakarsa subdsitrict. The method used is descriptive. Refill drinking water samples was taken and tested in the MPN (Most Probable Number) method and then to be tested in identification of E. coli. The results of testing the drinking water refill obtained 15 samples positive for coliform bacteria. Samples were positive for E. coli bacteria that sample B.1 and F.2.